Outpatient volumes and medical staffing resources as predictors for continuity of follow-up care during transfer of adolescents with congenital heart disease. (1st July 2020) - Skogby, Sandra; Moons, Philip; Johansson, Bengt; Sunnegårdh, Jan; Christersson, Christina; Nagy, Edit; Winberg, Per; Hanséus, Katarina; Trzebiatowska-Krzynska, Aleksandra; Fadl, Shalan; Fernlund, Eva; Kazamia, Kalliopi; et al.
Abstract: Background: Providing continuous follow-up care to patients with congenital heart disease (CHD) remains a challenge in many settings. Previous studies highlight that patients with CHD experience discontinuation of follow-up care, but mainly describe a single-centre perspective, neglecting inter-institutional variations. Hospital-related factors above and beyond patient-related factors are believed to affect continuity of care. The present multicentre study therefore investigated (i) proportion of "no follow-up care"; (ii) transfer destinations after leaving paediatric cardiology; (iii) variation in proportions of no follow-up between centres; (iv) the association between no follow-up and outpatient volumes, and (v) its relationship with staffing resources at outpatient clinics. Methods: An observational, multicentre study was conducted in seven university hospitals. In total, 654 adolescents with CHD, born between 1991 and 1993, with paediatric outpatient visit at age 14-18 years were included. Transfer status was determined 5 years after the intended transfer to adult care (23y), based on medical files, self-reports and registries. Results: Overall, 89.7% of patients were receiving adult follow-up care after transfer; 6.6% had no follow-up; and 3.7% were untraceable. Among patients in follow-up care, only one remained in paediatric care and the majority received specialist adult CHD care. Significant variability in proportions of no follow-up were identified across centres. Higher outpatient volumes at paediatric outpatient clinics were associated with better continued follow-up care after transfer (OR = 1.061; 95% CI = 1.001 – 1.124). Medical staffing resources were not found predictive. Conclusion: Our findings support the theory of hospital-related factors influencing continuity of care, above and beyond patient-related characteristics. Graphical abstract: Unlabelled Image Highlights: The majority of patients (83.7%) received specialist ACHD care after transfer. Only one patient remained in paediatric care after 23 years of age. Larger paediatric outpatient volumes increase odds of follow-up in adult care. Outpatient staffing resources were not predictive for follow-up after transfer.